Timescales and drivers of chlorophyll variability in a subtropical, long residence time estuary (Baffin Bay, Texas, USA) - Emily K. Cira; Laura Beecraft; Michael S. Wetz (PLoS ONE, 2025)
Little is known about the role of short-term (hourly to daily) processes on estuarine phytoplankton dynamics, though these can be important timescales of physical-chemical variability in coastal systems. This study coupled high-frequency (daily; 2015–2016) and low frequency (monthly; 2014–2018) sampling to quantify timescales of chlorophyll variability and potential drivers of phytoplankton blooms in a subtropical, long residence time estuary (Baffin Bay, Texas, USA). The dominant timescale of chlorophyll variability in the system was sub-monthly, which accounted for ~ 37% of variability, followed by interannual at ~ 30% and seasonal at 21%. From bloom events identified in the high frequency dataset, wind was a predominant factor related to short-term (daily resolution) blooms, often positively correlated with chlorophyll concentrations. Results expand upon the currently limited knowledge of short-term chlorophyll variability in subtropical, long residence time estuaries. Additionally, findings also offer insight into design considerations for sampling programs in similar systems.